Construction of sanitation and refuse disposal system for Sekolah Rendah Agama (SRA) / Luqman Nul Hakim Ab Razak - Ab Razak, Luqman Nul Hakim (UiTM Perak Press, 2015)
Teamcoat Engineering Sdn Bhd is located in Selayang. Meanwhile, Selayang is a town which is located in Gombak district in a state of Selangor. The town is located around 10 km northwest from Kuala Lumpur, and also a few kilometers from Kepong, Rawang and Batu Caves. A new township, Bandar Baru Selayang is located just 2 km away and was named after the town, where Majlis Perbandaran Selayang is located. Selayang is mostly administered by the Majlis Perbandaran Selayang (MPS) and part of the town that’s spills over into the Federal Territory of Kuala Lumpur is administered by Dewan Bandaraya Kuala Lumpur (DBKL). Teamcoat Engineering Sdn Bhd (TC) is located in Selayang Pandang which is administered by MPS. TC is located near the Caltex station at Selayang Pandang. The distance between TC and Caltex Station is only around 500 metres. The company was established at 1992 and the owner of the company is Dato Ir. Haji Mohd Nasir Bin Ibrahim. Nature of the company business is construction and building maintenance, water proofing, specialist in painting, floor coating, demolishing work, water work, concrete repair, and structure strengthening.